2016
DOI: 10.1016/j.molcel.2016.01.027
|View full text |Cite
|
Sign up to set email alerts
|

SH2 Domains Serve as Lipid-Binding Modules for pTyr-Signaling Proteins

Abstract: SUMMARY The Src-homology 2 (SH2) domain is a protein interaction domain that directs myriad phosphotyrosine (pY) signaling pathways. Genome-wide screening of human SH2 domains reveals that ≈90% of SH2 domains bind plasma membrane lipids and many have high phosphoinositide specificity. They bind lipids using surface cationic patches separate from pY-binding pockets, thus binding lipids and the pY motif independently. The patches form grooves for specific lipid headgroup recognition or flat surfaces for non-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 54 publications
2
97
0
Order By: Relevance
“…tSH2 showed detectable association with the membrane on PLL-coated surfaces (Supplementary Fig. 1k and Supplementary Video 8), which suggested that nonspecific binding caused increased tSH2 diffusion and span trajectories 36 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…tSH2 showed detectable association with the membrane on PLL-coated surfaces (Supplementary Fig. 1k and Supplementary Video 8), which suggested that nonspecific binding caused increased tSH2 diffusion and span trajectories 36 .…”
Section: Resultsmentioning
confidence: 95%
“…TCR-independent binding of Zap70 to the plasma membrane could take place through interactions with other membrane-associated proteins via its SH2 domains or phosphorylated tyrosine residues 46,47 . Alternatively, the carboxy-terminal SH2 domain of Zap70 contains a lipid-binding site for phosphatidylinositol trisphosphate and phosphatidylinositol-(4,5)-bisphosphate that is required for T cell activation and could facilitate direct membrane binding upon Zap70's release 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these findings have remained controversial as they lacked mechanistic details. In a recent study, Park and colleagues took on the challenge and systematically evaluated the role of lipids in regulating SH2 domain-mediated protein-protein interactions and downstream signaling events [16**]. They provided sound evidence that most SH2 domains bind with high affinity to PM lipids through their so-called “alternate cationic patches” (ACPs), which are domains adjacent to hydrophobic and/or aromatic residues reminiscent of membrane-binding protein lipid-binding sites (Figure 1b).…”
Section: Membrane Lipid Composition and Cell Signalingmentioning
confidence: 99%
“…This point is signified by recent findings in which classical PPI domains (e.g., SH2 domains) were shown to bind to negatively charged lipids as described in the following section. [16] …”
Section: Current Model Of Biological Signaling As Bow Tie-shaped Pmentioning
confidence: 99%
“…Previous work has demonstrated the presence of positively charged surface regions on SH2 domains that are distinct from known phosphopeptide/protein binding sites. [16] These cationic surface patches may provide an interaction surface for negatively charged lipids in membrane bilayers and, as a result, facilitate sequestration of the SH2 domain-containing protein to plasma or organelle membrane surfaces. A recent study by Park et al examined such interactions between negatively charged phosphoinositides (PIs) and 76 human SH2 domains by surface plasmon resonance (SPR).…”
Section: Sh2 Domain As a Membrane Binding Modulementioning
confidence: 99%